Penatalayanan Ibadah Terbatas Pada Masa Pandemi Covid-19 - Erman Saragih (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2021)
This article has an idea about the arrangement of limited worship (individuals) during the covid-19 pandemic. In this article, the functions of obedience theology, the construction of koinonia, and the liturgy of perichoresis are sub-discussed. The lens of discussion about theology during the Covid-19 pandemic. Empirically, worship at home is a massive and proactive solution. The capacity of worship at home is always carried out in a hierarchical liturgical pattern. Koinonia as a spirit relation of communal communion is constructed as a model for the church of individual koinonia. The method used is a literature study, specifically content analysis with the principle of systematic literature review. The conclusion that I convey is first, obedience theology as the basis of Christian spiritual ethics. Second, the early church fellowship pattern emphasized dynamic power by the apostles so that they were able to endure and overcome obstacles. Third, proactive fellowship becomes a common model to survive and start thinking about the future of the church. Fourth, individual worship liturgies can consider the principle of the perichoresis relation to delay the hierarchical pattern of worship. Artikel ini menyoal tentang penatalayanan ibadah terbatas (di rumah) pada masa pandemi covid-19. Pada artikel ini fungsi teologi ketaatan, konstruksi koinonia, dan liturgi perikoreisis menjadi sub pembahasan. Lensa pembahasan seputar teologi di masa pandemi Covid-19. Secara empiris, ibadah di rumah menjadi solusi masif dan bersifat proflektif. Kapasitas ibadah di rumah selalu dilakukan dalam pola liturgi hierarkis. Koinonia sebagai relasi spirit persekutuan komunal dikonstruksi menjadi model menggereja koinonia individual. Metode yang dilakukan menggunakan studi literatur secara khusus analysis content dengan prinsip tinjuan literatur secara sistematis. Kesimpulan yang saya sampaikan adalah pertama, teologi ketaatan sebagai basis etis spritual ibadah terbatas. Kedua, pola persekutuan gereja mula-mula menekankan kuasa dinamis oleh para rasul sehingga mampu bertahan dan melampaui hambatan. Ketiga, persekutuan Proflektif menjadi model bersama untuk bertahan dan mulai memikirkan masa depan gereja. Keempat, liturgi ibadah individual dapat mempertimbangkan prinsip relasi perikoresis untuk menunda hierarkisasi pola ibadah.